Produção do sorgo sacarino na região do Cariri - CE - Silva, Josefa Maria Francieli da (2017)
The Sorghum bicolor L. Moench is an excellent alternative to sugarcane for the production of biofuels, because it has high concentrations of sugar in the stalks, can be processed in the same facilities and has a short production cycle. The objective of this work was to evaluate the effect of plant arrangement, through the combination of spacing between lines and plant population, as well as the effect of sowing and cutting times in the Cariri Cearense region. The trials were conducted in the experimental area of the Center of Agrarian Sciences and Biodiversity of the Federal University of Cariri. The experimental design was a randomized block design (DBC), with four replications, in a subdivided plot scheme. The plots were composed of three spacings (70, 80 and 90 cm), and the subplots by four sorghum plant populations (80,000, 100,000, 120,000 and 140,000 ha-1 plants). The following variables were analyzed: plant height, stalk diameter, fresh stem mass, leaves, panicles and total, dry mass of stalks, leaves, Panicles and total, broth volume, ºbrix, total soluble sugars and reducing. The results were submitted to analysis of variance and the means of the treatments when necessary were compared by the Tukey test at 5% of significance in Sisvar. The models for adjusting the equations were chosen based on the coefficient of determination and the significance of the effects. The results showed that there was a significant interaction between the factors between row spacing and plant populations for reducing sugars. Isolated effects for plant population factor: plant height, stalk diameter, stem dry mass and reducing sugars. The factor between lines: fresh stem mass, fresh leaf mass, dry mass of panicles and total fresh mass, volume of broth. There was no significant effect for the total soluble solids (Brix) and fresh mass of the panicles and total dry mass. It is concluded that the most suitable population arrangement for the cultivation of sorghum in the Cariri region of Ceará for the production of ethanol is a population of 120 thousand plants per hectare with spacing between rows of 70 centimeters planted in the second season of sowing with cut at 120 days after planting.